Non-wage benefits, costs turnover, and labor attachment: evidence from Russian firms - Tuuli Juurikkala; Olga Lazareva (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
Just as in established market economies, many Russian firms provide non-wage benefits such as housing, medical care or day care to their employees.Interpreting this as a strategic choice of firms in an imperfect labor market, this paper examines unique survey data for 404 large and medium-size industrial establishments from 40 Russian regions.We find strong evidence that Russian industrial firms use social services to reduce the costs of labor turnover in the face of tight labor markets.The strongest effect is observed for blue-collar workers.We also find that the share of non-monetary compensation decreases with improved access to local social services.
URN:NBN:fi:bof-201408072135
Keywords: J32; J33; J42; J63; M52; P31; 330; Non-wage benefits; labor turnover; labor attachment; Russia